Orientalism in Washington Irving’s Creativity (Eurasian Journal of Philology Science and Education, 2018)
In the article is considered Orientalism in the works of the famous American writer Washington Irving. During Washington Irving’s years in Europe, he maintained his interest in Spain both as a literary subject and as a nation. Irving believed that the Arabs played an important positive role in the development of the culture of Spain. As you know, numerous literary works devoted to the Muslim culture of the Middle Ages of Spain draw attention to the historical reality of works, idealizing the description of events. Washington Irving in the book The Life of Mahomet and His Successors, as well as in his works on the East, such as The Chronicle of the Conquest of Granada and The Alhambra, reflects the history and geography of the East, folklore and ethnic-culture, religious and Spiritual way of life, customs and traditions, and in this there is a deep knowledge of the author, the psychology of the eastern man.